Implementasi Metode Delta-Extract untuk Sinkronisasi Data Pada Aplikasi Kasir Smart Laundry Assistant and Management (SINADME) (Studi Kasus: CV. Citridia IT Solution) - Shidqon Alkaaf; Satrio Agung Wicaksono; Aryo Pinandito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Database synchronization is an activity to equalize the data contained in multiple databases. It is utilized by the SINADME Mobile app in the process of retrieving primary data on servers temporarily stored in mobile applications for offline transactions. Currently SINADME Mobile uses the Full-Load method to synchronize, so if sync is done on a regular basis it will result in increased load. This research will implement Delta-Extract method in synchronizing to reduce load during synchronization routinely. The focus of this research is the analysis of the loads received by mobile applications using Full-Load and Delta-Extract. Based on the test results, the Full-Load Method eases the burden received by the mobile application during initial data retrieval and the Delta-Extract method reduce the loads received by the mobile application during data retrieval after changes.